An Assessment of Student Moral Development at the National Defense University: Implications for Ethics Education and Moral Development for Senior Government and Military Leaders. Issue 4 (1st October 2020) - Agrawal, Raj; Williams, Kenneth; Miller, B. J.
ABSTRACT: Senior service colleges provide professional education to prepare military and government civilians for public service at the senior levels of strategy and policy. Inclusive in the program of study is ethics education, since various constituents expect their leaders to act in an ethical manner and to incorporate ethics and values in decision-making, policy, and strategy. In order to develop the most effective professional ethics education, the National Defense University assessed students in a pre- and post-test format using the Defining Issues Test Version 2 to determine their patterns of moral judgment at the beginning and the conclusion of the program. This article discusses the theoretical background, existing research, results, and implications of the study. Key findings include military students aligning with the Maintaining Norms schema; civilian students aligning with the Postconventional schema; and no significant changes as a result of the program. The article concludes with recommendations for ethics education for military and public service professionals. This research helps fill a void of empirical data on the moral development of military and public servants.